Do information systems meet the needs of primary care trusts? - Diane Jones; David Wilkin (Journal of Innovation in Health Informatics, 2003)
To function effectively, primary care trusts (PCTs) need information from a range of sources. The general practice clinical record is a key source of information for PCTs but has often proved to be of variable quality. PCTs have developed rapidly and now have responsibility for 75% of the healthcare budget. They have a range of information needs that must be met if they are to ensure that healthcare provision meets the needs of patients. Since the abolition of health authorities PCTs have full responsibility for developing practice systems as well as having a key role to play in developing information management and technology (IM&T) within local health economies. The paper describes the problems PCTs face in accessing information to support their core functions and the progress they have made in retrieving data to support service development. It also describes the progress and developments in information and information systems within general practice using data from the National Tracker Survey of Primary Care Groups and Trusts (PCG/Ts). The survey began in 1999 when PCGs were established and has tracked the progress of PCG/Ts over three years. This paper presents the findings from the third survey relating to the development of information to support the needs of PCG/Ts. The findings show that information available to PCG/Ts does not meet their needs in a range of key areas. Many PCG/Ts are collecting data to support the Coronary Heart Disease National Service Framework (CHD NSF) and monitoring some areas of service provision in general practice. The use of information management tools has risen significantly since the second survey and involvement in the Primary Care Information Services (PRIMIS) initiative has more than doubled. The paper concludes that although PCG/Ts and general practices have made substantial progress, there is a long way to go before information providers generate high-quality information to support the needs of PCTs.